Symbolic annihilation of Syrian refugees by Turkish news media during the COVID-19 pandemic - Yucel, Alev (Bmc, 2021)
Background This article presents a discussion about the representation of Syrian refugees in Turkish news media during the COVID-19 pandemic. Media play a critical role during pandemics by affecting values, opinions, public knowledge about stigmatized groups. When media ignore and stereotypically represent a social group, the social value of the group decreases, and their problems are trivialized. Method I analyzed data provided by Media Monitoring Center which is an independent media company in Turkey. Sample was selected to reveal news representation of Syrian refugees between March 11, 2020 (the first confirmed case of COVID-19 in Turkey) and August 20, 2020 (the time of this research). Mostly watched television evening (prime) news, the most widely circulated newspapers, and the most visited online news platforms were analyzed. By using content analysis method, the news stories about Syrian refugees were examined. Results It has been revealed that Turkish news media overwhelmingly acclaimed for Turkey's polices on Syrian refugees and the criticized the European Union policies towards refugees in the news stories. Even though almost 4 million Syrian refugees live in Turkey, with the largest refugee population in the world, Turkish news media ignored the plight of Syrian refugees. Conclusion Results of the study demonstrate that Syrian refugees were symbolically annihilated by Turkish news media during the COVID-19 pandemic. The concealment of information and symbolic annihilation of disadvantaged groups could potentially cause health disparities and irreparable harm to public health. Moreover, inequities exacerbate when predicaments of stigmatized groups are ignored in the news media. Further studies are needed to reveal the impact of the media on health disparities among stigmatized groups during the pandemics.
Keywords: Covıd-19 Pandemic; Symbolic Annihilation; Syrian Refugees; Turkey; Stigmatization; Media; Stigma; Epidemic; Crisis; Impact; Sars